Vision for the Future Project: Screening impact on the prevention and treatment of visual impairments in public school children in São Paulo City, Brazil (Clinics, 2021)
OBJECTIVES: Uncorrected refractive errors are the leading cause of visual impairment in children. In this cross-sectional retrospective study, we analyzed a social visual screening program for school children in São Paulo, Brazil, evaluated its impact on the prevention and treatment of children's visual disabilities, and assessed its epidemiological outcomes to outline suggestions for its improvement.METHODS: First-grade children from public schools were submitted to prior visual screening by their teachers. Selected children were forwarded to the hospital's campaigns for a second screening by ophthalmologists and treatment if needed. Data were analyzed for age, sex, visual acuity, biomicroscopy, refractive errors, ocular movement disorders, amblyopia, number of donated spectacles, and number of children forwarded to specialized care.RESULTS: A total of 1080 children were included with mean age of 6.24±0.45 years. Children with normal ophthalmological exam, 591 (54.7%; 95% confidence interval [CI]: 51.7%-57.7%) were dismissed and considered false-positives. Myopia, hyperopia, and astigmatism components were found in 164 (15.2%; CI: 13.1%-17.4%), 190 (17.6%; CI: 15.3%-20.0%), and 330 (30.5%; CI: 27.8%-33.4%) children, respectively. Amblyopia was diagnosed in 54 (5%; CI: 3.5%-6.4%) children, and 117 (10.8%; CI: 9.8%-12.8%) presented ocular movement disorders. A total of 420 glasses were donated.CONCLUSION: Epidemiological findings for amblyopia and refractive errors are consistent with those of similar studies. The expressive number of diagnoses performed and number of glasses donated to underprivileged children depict the importance of such projects. New guidelines to improve their cost-effectiveness, such as professional training and community sensitization, are imperative.